2014
DOI: 10.1186/2193-1801-3-266
|View full text |Cite
|
Sign up to set email alerts
|

Association between the serum concentration of triiodothyronine with components of metabolic syndrome, cardiovascular risk, and diet in euthyroid post-menopausal women without and with metabolic syndrome

Abstract: PurposeTo determine the association between the serum concentration of triiodothyronine (T3) with components of metabolic syndrome (MetS), cardiovascular risk (CVR), and diet in euthyroid post-menopausal women without and with MetS.MethodsA cross-sectional study was performed in 120 voluntary women of an indigenous population from Tlaxcala-México. Euthyroid status was assessed measuring the serum concentration of thyrotropin (TSH) and thyroid hormones, while that of estradiol was measured to confirm the postme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 42 publications
0
12
0
1
Order By: Relevance
“…Women were invited to the enrolment of our survey. This community forms part from the Otomies indigenous of México, and has a low income, low educational level, and nutritional deficiency …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Women were invited to the enrolment of our survey. This community forms part from the Otomies indigenous of México, and has a low income, low educational level, and nutritional deficiency …”
Section: Methodsmentioning
confidence: 99%
“…The BMI was calculated as the quotient of the body weight (kg) divided by the square of the height (m 2 ). Due to elderly subjects being commonly are shorter and slimmer as compared to their younger counterparts, the height was estimated by the half arm span . Fat mass was measured using a device to analyze the bioelectrical impedance (Tanita BC‐534, Inner Scan, IL, USA).…”
Section: Methodsmentioning
confidence: 99%
“…It suggested that fT3 level was correlated to the severity of HF in patients receiving CRT, which agreed with the previous studies. [17][18][19][20] Low fT3 level in HF reduced metabolic demand, which was seen as an adaptive process for HF. 21) But persistently low fT3 represented a maladaptive mechanism in favor of structural and functional cardiac remodeling, which had a key role in the pathogenesis of HF.…”
Section: Discussionmentioning
confidence: 99%
“…Low fT3 level reduced ejection fraction, and further caused enlarged heart chambers, lower velocity in the left atrial appendage and severe mitral regurgitation, which finally reduced cardiac systolic function. Thirdly, low-normal fT3 could affect several arteriosclerotic risk factors, such as diabetes mellitus, 17) insulin resistance, 20) serum lipid levels 23) and artery stiffness, 24) all of them above had been proved to have adverse effects on progress of HF. Fourthly, low fT3 status was independently correlated to peak oxygen uptake and functional exercise capacity in severe HF, which made recurrence of HF more frequent and remission period shorter than those with normal range of fT3.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies have reported that increases in TSH levels are associated with insulin resistance and clearly demonstrate that hypothyroidism is linked to increases in insulin resistance (9,134). Even modest increases in TSH are associated with subclinical hypothyroidism, and are correlated with insulin resistance and hyperlipidemia (15,59,68,77). TSH has the capacity to directly induce adipogenesis, and PPAR␥ receptor agonism can potently stimulate TSH receptor expression and adipogenesis (125).…”
Section: Hypothyroidism and Insulin Resistancementioning
confidence: 99%